2010
DOI: 10.1002/fld.2221
|View full text |Cite
|
Sign up to set email alerts
|

Space–time finite element computation of complex fluid–structure interactions

Abstract: SUMMARYNew special fluid-structure interaction (FSI) techniques, supplementing the ones developed earlier, are employed with the Stabilized Space-Time FSI (SSTFSI) technique. The new special techniques include improved ways of calculating the equivalent fabric porosity in Homogenized Modeling of Geometric Porosity (HMGP), improved ways of building a starting point in FSI computations, ways of accounting for fluid forces acting on structural components that are not expected to influence the flow, adaptive HMGP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 66 publications
1
90
0
Order By: Relevance
“…With this technique, we can reduce the FSI computational effort where we do not need it and increase the accuracy of the structural mechanics computation where we need accurate, detailed structural mechanics computations, such as computing the fabric stresses in a parachute FSI. Test computations for parachute modeling, with different purposes of using the SCFSI M2C technique, were presented in [59,63,110].…”
Section: Remark 38mentioning
confidence: 99%
“…With this technique, we can reduce the FSI computational effort where we do not need it and increase the accuracy of the structural mechanics computation where we need accurate, detailed structural mechanics computations, such as computing the fabric stresses in a parachute FSI. Test computations for parachute modeling, with different purposes of using the SCFSI M2C technique, were presented in [59,63,110].…”
Section: Remark 38mentioning
confidence: 99%
“…The FSI computations reported in 2009 [64][65][66] and 2010 [67][68][69][70][71][72][73] were for detailed parachute and artery analysis. The detailed studies were mainly on cerebral arteries with aneurysm, Orion spacecraft parachutes, and reefed stages of the Orion spacecraft parachutes.…”
Section: Years 2001-2010mentioning
confidence: 99%
“…Some of the successful studies include those reported in [28,27,24,29,25,26], where the Deforming-SpatialDomain/Stabilized Space-Time (DSD/SST) method [34,35] was used in [27,24,29,25,26]. The studies in [37,36,31,32,38] also used the DSD/SST as the core numerical method, but involved new versions and special techniques. These studies successfully addressed the computational challenges in handling the geometric complexities of the parachute canopy and the contact between parachutes in a cluster.…”
Section: Modelling Of Parachute Canopymentioning
confidence: 99%